C5a Regulates IL-12(+)DC Migration to Induce Pathogenic Th1 and Th17 Cells in Sepsis - Ma, Ning (Public Library of Science, 2013)
OBJECTIVE: It is well known that complement system C5a is excessively activated during the onset of sepsis. However, it is unclear whether C5a can regulate dentritic cells (DCs) to stimulate adaptive immune cells such as Th1 and Th17 in sepsis. METHODS: Sepsis was induced by cecal ligation and puncture (CLP). CLP-induced sepsis was treated with anti-C5a or IL-12. IL-12(+)DC, IFNγ(+)Th1, and IL-17(+)Th17 cells were analyzed by flow cytometry. IL-12 was measured by ELISA. RESULTS: Our studies here showed that C5a induced IL-12(+)DC cell migration from the peritoneal cavity to peripheral blood and lymph nodes. Furthermore, IL-12(+)DC cells induced the expansion of pathogenic IFNγ(+)Th1 and IL-17(+)Th17 cells in peripheral blood and lymph nodes. Moreover, IL-12, secreted by DC cells in the peritoneal cavity, is an important factor that prevents the development of sepsis. CONCLUSION: Our data suggests that C5a regulates IL-12(+)DC cell migration to induce pathogenic Th1 and Th17 cells in sepsis.